The Mediation Role of Customer Satisfaction in Building Coffee Lover Loyalty Driven by Service Quality Management - Agus Usman; Andi Wijaya; Agung Zulfikri (Eastasouth Institute, 2026)
This study investigates the effect of service quality on customer loyalty, with customer satisfaction serving as a mediating variable for coffee shop customers. Using a structured questionnaire, Structural Equation Modeling (SEM) was employed to analyze data collected from coffee shop customers. The mediation results indicate that when superior service quality leads to a satisfying consumption experience, customers are more likely to become loyal. This indicates that customer satisfaction and customer loyalty are directly influenced by service quality. One way to foster customer loyalty through customer satisfaction in the coffee shop industry is through integrated service quality checks, according to recent research. This study differs from previous research that primarily focused on direct effects; instead, it highlights a crucial mechanism through which customer satisfaction transforms perceptions of quality into customer loyalty.